Kapitalizm państwowy jako dylemat praktyczny i teoretyczny - Nowakowski, Krzysztof (Wydział Prawa i Administracji UAM, 2014)
W wielu krajach następuje współwystępowanie rynków oraz państwa o obliczu autorytarnym. Kapitalizm państwowy to system ekonomiczno-społeczny, w którym rządy manipulują rynkiem dla swoich celów politycznych. W ogólnych obawach bezpośrednie inwestycje zagraniczne, firmy i fundusze państwowe, realizują swoje polityczne i geostrategiczne plany bardziej niż te o charakterze rynkowym. Współczesny kapitalizm państwowy nie jest nowym zjawiskiem, ale następstwem globalnego kryzysu, który powoduje wzrost udziału państwa. Zatem pytanie brzmi, czy kapitalizm państwowy zmienia w sposób konceptualny i praktyczny dotychczasowy kapitalizm wolnorynkowy i stanowi atrakcyjną alternatywę dla rozwijających się gospodarek. Firmy państwowe i fundusze państwowe raczej adaptują warunki rynkowe, niż realizują założenia polityczne. Kapitalizm państwowy to nie jest nowy typ systemu ekonomicznego ani teorii ekonomicznej. Wykazuje swoje słabości. Jeśli rząd faworyzuje swoje jednostki, koszty tego ponoszą producenci i konsumenci (koszty alternatywne). Kapitalizm państwowy nie gwarantuje stabilności i jest efektywny, jeśli państwo jest efektywne. Kapitalizm państwowy wydaje się polityczną i ekonomiczną rzeczywistością, ale musi się zmagać z rozwijającą się i zdywersyfikowaną gospodarką rynkową. W tej perspektywie to droga do dobrobytu przez zastosowanie nieortodoksyjnych narzędzi ekonomicznych.

***In many countries we observe co-existence of markets and states of an authoritarian face. State capitalism is an economic-social system in which governments manipulate market outcomes for political purposes. There is a wide-spread fear that foreign direct investment, state owned enterprises and sovereign wealth funds are guided in their decisions by political and geostrategic rationales rather than by the traditional marked-oriented mind frame, thus distorting competition. Contemporary state capitalism is not a new phenomenon but an aftermath of the recent global crisis which seems to have legitimised the renaissance of state capitalism. Consequently, many economies see their governments resort to stronger roles. In this paper the question we ask is whether state capitalism changes free-market capitalism conceptually and practically and whether it offers, instead, an attractive alternative to emerging economies. State owned enterprises and sovereign wealth funds adapt to market conditions rather than seek to realise their political goals. State capitalism is not a new type of an economic system but a new category that can be treated within the existing theoretical frameworks. Yet, a close look at the model shows its weaknesses. When the government favours its own entities, the other suffer, and the producers and consumers pay (alternative costs). State capitalism does not guarantee stability and works well only when directed by a competent state. State capitalism seems to be a political and economic reality but it must be treated as a stage in the development of diversified market economy. In this perspective, state capitalism is the road to prosperity through the use of unorthodox economic tools.
State capitalism – a practical and theoretical dilemma
Keywords: kapitalizm państwowy; firmy państwowe; państwowe fundusze finansowe; state capitalism; state-owned enterprises (SOE); sovereign wealth fund (SWF)